Mechanical characterisation and flexural performance of eco-friendly concrete produced with fly ash as cement replacement and coconut shell coarse aggregate. (29th April 2019) - Prakash, R.; Thenmozhi, R.; Raman, S.N.
The aim of this study is to investigate the effect of adding fly ash, an industrial by-product and coconut shell, an agricultural waste on the mechanical and flexural characteristics of eco-concrete. The study focuses on density, compressive strength, tensile strength and flexural behaviour of the coconut shell eco-concrete. Two different mixes are developed, one with coconut shell and the other with conventional aggregate and coconut shell as coarse aggregate. The cement content is replaced with class F fly ash at 0%, 10%, 20% and 30% by weight. The test result shows that the coconut shell concrete produced with 10% fly ash has recorded higher compressive, tensile strength than other proportions. Fly ash inclusion further reduces the density of coconut shell concrete. The higher deflection of coconut shell concrete before failure shows that it has failed in a ductile manner. The flexural behaviour is comparable with other lightweight concretes. It is suggested that an eco-friendly, cost effective structural lightweight concrete can be produced by using coconut shell and fly ash.